Community Religion, Employees, and the Social License to Operate - Cui, Jinhua (Journal of business ethics, 2016)
The World Bank recently noted: “Social license to operate has traditionally referred to the conduct of firms with regard to the impact on local communities and the environment, but the definition has expanded in recent years to include issues related to worker and human rights” (World Bank 2013, http://go.worldbank.org/FZ88VMOM90). In this paper, we examine a factor that can influence the kind of work conditions that can facilitate or obstruct a firm’s attempts to achieve the social license to operate (SLO). Specifically, we examine the empirical association between a company’s employee practices and the religiosity of its local community by investigating their fixed and endogenous effects. Using a large and extensive U.S. sample, we find a positive association between the “employee friendly” practices of a firm and the religiosity of the local community after controlling for several firm characteristics. In addition, after mitigating endogeneity with the dynamic panel system generalized method of moment and after employing several other econometric tests, we still find a robust positive association between the religiosity of the local community and employee-friendly practices. Since recent research has shown that the firm’s treatment of its stakeholders is a key to achieving an SLO, and since employees constitute a highly significant stakeholder group, we interpret our results as supporting the view that religion is an important influence on the kinds of employee practices that can increase the likelihood that a firm will acquire the SLO.